Serials use at Babcock University Library, Ilisan-Remo, Ogun State, Nigeria (2008 – 2012) - Madukoma, Ezinwayi; ., Itunu A. Bamidele; ., Saturday U.Omeluzor (Information Management and Business Review, 2013)
This study highlights the intensity of print serials utilized at Babcock University library from 2008 to 2012. The study only takes account of print serials subscribed to and made available at the serials department of the library. The result of the study revealed that serials recorded the highest level of use in 2008, the lowest utilization occurred in 2012. Serials in social sciences, medical science and religion as well as magazines/newsletters, were the most utilized. There were also indications from the findings that print serials have continued to support learning, teaching and research. Therefore, the researchers concluded that subscription to print serials should be on-going. Librarians should also endeavor to create more awareness and encourage patrons’ use of print serials.